CLAIMS, HISTORIES, MEANINGS: INDIGENEITY AND LEGAL PLURALISM IN INDIA - POOJA PARMAR (UNIVERSITY OF BRITISH COLUMBIA, 2012)
This dissertation offers critical insights into issues of access to justice by tracing the gains and losses in meaning across multiple accounts of a dispute that began with Adivasi protests against Hindustan Coca‐Cola Beverages Private Ltd. in a village in Kerala in South India. A sit‐in agitation started by Adivasi residents of the area in 2002, soon after the company set up a beverage bottling plant in the middle of small hamlets and began extracting large amounts of groundwater, is now in its tenth year. The juxtaposition of the various popular, legal and Adivasi accounts of this dispute enables a closer look at the ways in which meanings change as claims originating in contested, layered histories and in the narratives of displacement and exclusion are translated into the stronger languages of social movements and the formal legal system. Much of the particular and situated meanings, critical to the Adivasis’ experience of injustice and their opposition to the operation of the Coca‐Cola plant, have been eclipsed in the accounts of their many committed supporters, more often than not, in pursuit of justice for the Adivasis. In addition to drawing attention to the practices and processes of literal and conceptual translation, the stories presented here demonstrate that when Adivasi protests against Coca‐Cola are understood on their own terms, in the context of their lives in the place and the stories they tell, the meanings that emerge are quite different from the ones that the available popular and legal accounts convey about these protests. They also indicate that a recognition of this difference is important for a meaningful resolution of this dispute for those whose lives have been most affected by it.